The Gypsy ‘Menace’: Populism and the New Anti-Gypsy Politics - Tina Magazzini (Slovo, 2013)
The Gypsy ‘Menace’: Populism and the New Anti-Gypsy Politics. Edited by Michael Stewart. Pp. 311. London: Hurst & Company. 2012. £18.95. Paperback. ISBN: 9781849042208. Click here to read the review